1991
DOI: 10.1104/pp.95.4.1181
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of Arabidopsis with Altered Regulation of Starch Degradation

Abstract: Mutants of Arabidopsis thaliana (L.) Heynh. with altered regulation of starch degradation were identified by screening for plants that retained high levels of leaf starch after a period of extended darkness. The mutant phenotype was also expressed in seeds, flowers, and roots, indicating that the same pathway of starch degradation is used in these tissues. In many respects, the physiological consequences of the mutations were equivalent to the effects observed in previously characterized mutants of Arabidopsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
225
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(245 citation statements)
references
References 25 publications
(39 reference statements)
18
225
2
Order By: Relevance
“…Both fimmric acid (Fig. 4) and starch (Caspar et al 1991) levels also increase at higher light intensities. High light intensities may increase fiunaric acid levels by increasing photosynthetic rates.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Both fimmric acid (Fig. 4) and starch (Caspar et al 1991) levels also increase at higher light intensities. High light intensities may increase fiunaric acid levels by increasing photosynthetic rates.…”
Section: Discussionmentioning
confidence: 86%
“…Light has been shown to activate phosphoermlpyruvate carboxylase kinase leading, in turn, to higher levels of phosphoenolpyruvate carboxylase activity (Li et al 1996). Furnaric acid (Table 2) and starch (Caspar and Pickard 1989;Caspar et al 1991) also show similar distribution patterns, as both accumulate to high levels in leaves, stems and developing siliques of Arabidopsis, but are low in mature seeds and in roots. However, furnaric acid and starch levels do not always fluctuate in parallel.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…; Caspar et al, 1991), has been isolated and extensively analyzed. It was suggested that SEX1 may play a role in starch degradation.…”
Section: Several Starch Metabolic Mutants Of Arabidopsis Are Delayed mentioning
confidence: 99%